VALIDITAS MEDIA PEMBELAJARAN FLIP CHART PADA MATERI EKOSISTEM KELAS X JENJANG SMA - Desy Alfianita; Kaspul Kaspul; M. Arsyad (Khazanah Pendidikan, 2022)
Learning media is needed because the media can be used as tools or additional teaching materials in addition to textbooks and worksheets. The use of learning media can increase students' motivation and interest in learning. Ecosystem material flip chart media is expected to be a solution in the learning process so that not only teachers but also students are active in the learning process. This study aims to describe the validity of flip chart learning media in class X ecosystem material. This study uses Research and Development (R & D) research methods and the ADDIE development model, through the stages of analysis (analyze), design (design), development (development) and implementation (implementation). The validity test was obtained from 3 validators according to their expertise. The data was obtained through an assessment instrument in the form of a validity assessment sheet. The results of this study indicate that flip chart learning media obtained an average validity value of 91.67% on the physical appearance aspect, 96.67% on the illustration aspect, 94.43% on the media quality aspect, and 100% on the attractiveness aspect. Based on the values obtained from the four aspects, the overall average value was 94.44%, so it can be concluded that the flip chart learning media has a very valid category.